Bank regulations and income inequality: Empirical evidence - Manthos D. Delis; Iftekhar Hasan; Pantelis Kazakis (Bank of Finland, 2012)
This paper provides cross-country evidence that variations in bank regulatory policies result in differences in income distribution. In particular, the overall liberalization of banking systems decreases the Gini coefficient and the Theil index significantly. However, this effect fades away for countries with low levels of economic and institutional development and for market-based economies. Among the different liberalization policies, the most significant negative effect on inequality is that of credit controls, which also seem to have a lasting effect on the Gini coefficient. Banking supervision and the abolition of interest rate controls also have a negative yet short-run impact on income inequality. A notable finding is that liberalization of securities markets increases income inequality substantially and over a long time span, suggesting that securitization widens the distribution of income. We contend that these findings have new implications for the effects of bank regulations, besides those related to their impact on financial stability.
URN:NBN:fi:bof-20140807148
Keywords: G28; O15; O16; 330; Bank regulations; Income inequality; Cross-country panel data; Instrumental variables; Panel VAR